IN VITRO ANTI-MALARIAL ACTIVITY OF RHIZOME EXTRACTS OF CURCUMA SPECIES - PRASANTHI DONIPATI,; DR.S.HARASREERAMULU,; DR.S.HARASREERAMULU, (International Journal of Pharma and Bio Sciences, 2015)
Malaria is a major parasitic disease that is transmitted to humans by Anopheles mosquitoes and is responsible for deaths each year in many tropical and subtropical regions. The aim of this study was to assess the efficacy of Chloroquine in the treatment of Plasmodium vivax malaria in Curcuma species. Malaria parasite (Plasmodium vivax) was used in this study. Parasitemia was cultured in RPMI 1640 culture medium (with 10% human serum and gentamycin 2µg/ml) at 37°C in 5% CO2 incubator. To test the anti-malarial activity of plant extracts we used the susceptibility micro assay technique. Ethanolic extracts of Curcuma caesia, Hedychium coronarium, and Curcuma longa showed significant parasitaemia inhibitions ranging from 5.8-75.6%, 2.2-29%, 2-29.8% against the blood stage Chloroquine resistant P. vivax with negligible toxicity effect to parasitaemia cells in vitro. The extracts belonging to six plant species were able to perturb the growth of Chloroquine resistant P.vivax effectively. The findings justified the bioassay guided fractionation on these plants for the search of potent anti-malarial compounds or formulation of standardized extracts which may enhance the anti-malarial effect in vitro.